Canopy cover and ecological restoration increase natural regeneration of rainforest trees in the Western Ghats, India. Issue 5 (25th November 2021) - Osuri, Anand M.; Mudappa, Divya; Kasinathan, Srinivasan; Raman, T. R. Shankar
Abstract : Restoration of canopy cover through tree planting can assist in overcoming barriers to natural regeneration and catalyze recovery of degraded tropical forests. India has made international pledges to restore millions of hectares of degraded forests by 2030, but lacks empirical research on regeneration under different types of planted and natural overstories to guide this mission. We conducted a field study (65 plots of 25 m 2 ) to examine the influence of overstory type and canopy cover on naturally regenerating tree seedlings across degraded rainforests (DRs), mixed‐native species ecological restoration (ER) sites, monoculture eucalypt plantations (MP), and mature "benchmark" rainforests (BR) in the Western Ghats mountains of peninsular India. ER had higher native tree seedling densities and recovered community composition toward BR levels compared to DR, while communities in MP shifted in the opposite direction. Densities of native late‐successional species increased with canopy cover (particularly in ER), but greater canopy cover was also associated with increases in alien species, a few of which are shade‐tolerant. Further, in a nursery experiment comprising four rainforest species, seed germination and early survival increased with shade, but did not vary across soils originating from DR, ER, and MP. Our findings show that while improving canopy cover is important, doing so by planting diverse native species, and controlling invasive alien species, can benefit rainforest recovery in DR fragments. Conversely, planting non‐native monocultures in degraded forests, which is a prevalent practice in India, could prove counterproductive for forest recovery in the long term.